Загадка як алегоричний прийом у «Житії Ольги» - Герасимчук, С. (Літературознавчі обрії. Праці молодих учених, 2010)
«Olga’s Hagiography» is an encoded text, at the heart of which there are belles situations of foreign character qualified to create antithetic images of ingenious governess and short-sighted ancient people. The main method of creation the writing’s central motive, the motive of revenge, is the enigma as a peculiar allegorical way of trials, actuations which get their logical end in the death of defeated, due to the regular process of revenge forethought by the princess.